Rehabilitation and Physical Activity in Ehlers-Danlos Syndrome: A Review of Interventions and Outcomes - Stasiak, Michał; Woźniak, Karolina; Woźniak, Adam (Quality in Sport, 2025)
Purpose of Research: This study aims to explore the impact of physical activity on the quality of life of individuals with Ehlers-Danlos Syndrome (EDS), a group of disorders affecting connective tissues. The focus is on understanding how tailored exercise programs can improve symptoms and overall well-being across different EDS subtypes. Research Materials and Methods: A PubMed review identified studies on Ehlers-Danlos syndrome, quality of life, and exercise. Relevant peer-reviewed research from the last 20 years was included, screened, and synthesized. Basic Results: The findings indicate that physical activity plays a crucial role in improving the quality of life for individuals with EDS. Tailored exercise programs, including proprioceptive and stabilization exercises, have been shown to reduce pain and enhance functional capacity. Additionally, interdisciplinary approaches combining physical therapy with cognitive-behavioral strategies can mitigate psychological factors such as anxiety and depression, which are prevalent among EDS patients. Studies highlight the importance of adapting exercises to individual needs to avoid exacerbating symptoms like joint instability and chronic pain. Conclusions: In conclusion, physical activity is a vital component of EDS management, offering benefits in pain reduction, improved joint function, and enhanced quality of life. However, further research is necessary to determine the optimal exercise strategies for different EDS subtypes and to address the limitations of current studies, which often suffer from small sample sizes and heterogeneity in interventions. Developing personalized treatment plans that integrate physical therapy with psychological support can significantly improve patient outcomes and should be a priority in future studies. Additionally, there is a need to explore the effectiveness of interventions in pediatric and adolescent populations with EDS.